Multiomic analysis of human kidney disease identifies a tractable inflammatory and pro-fibrotic tubular cell phenotype - Maximilian Reck; David P. Baird; Stefan Veizades; Callum Sutherland; Rachel M. B. Bell; Heeyoun Hur; Carolynn Cairns; Piotr P. Janas; Ross Campbell; Andy Nam; Wei Yang; Nathan Schurman; et al. (Nature Communications)
Abstract Maladaptive proximal tubular (PT) epithelial cells have been implicated in progression of chronic kidney disease (CKD), however the complexity of epithelial cell states within the fibrotic niche remains incompletely understood. Hence, we integrated snRNA and ATAC-seq with high-plex single-cell molecular imaging to generate a spatially-revolved multiomic atlas of human kidney disease. We demonstrate that in injured kidneys, a subset of HAVCR1 + VCAM1 + PT cells acquired an inflammatory phenotype, upregulating genes encoding chemokines, pro-fibrotic and senescence-associated proteins and adhesion molecules including ICAM1. Spatial transcriptomic and multiplex-immunofluorescence determined that specifically these VCAM1+ICAM1+ inflammatory PT cells localised to the fibrotic niche. Ligand-receptor analysis highlighted paracrine signaling from inflammatory PT cells mediating leucocyte recruitment and myofibroblast activation. Loss of HNF4α and activation of NF-κβ and AP-1 transcription factors epigenetically imprinted the inflammatory phenotype. Targeting inflammatory tubular cells by administering an AP-1 inhibitor or senolytic agent ameliorated inflammation and fibrosis in murine models of kidney injury, hence these cells may be a tractable target in CKD.